2005
DOI: 10.1590/s0100-06832005000500004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil pH on inorganic phosphorus sorption and desorption in a humid brazilian Ultisol

Abstract: SUMMARYLiming is a common practice to raise soil pH and increase phosphorus (P) bioavailability in tropical regions. However, reports on the effect of liming on P sorption and bioavailability are controversial. The process of phosphorus desorption is more important than P sorption for defining P bioavailability. However few studies on the relationship between soil pH and P desorption are available, and even fewer in the tropical soils. The effects of soil pH on P sorption and desorption in an Ultisol from Bahi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 22 publications
2
43
0
4
Order By: Relevance
“…Loganathan et al (1987) reported similar observation in some soils from southern Nigeria. It also seems that soil pH has pronounced influence on phosphorus availability in weathered tropical soils only under conditions of high phosphorus levels attained by addition of phosphorus solution to soil (Eze and Loganathan, 1990), or when soils are treated with liming materials to enhance normal distribution of their pH values (Sato and Comerford, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loganathan et al (1987) reported similar observation in some soils from southern Nigeria. It also seems that soil pH has pronounced influence on phosphorus availability in weathered tropical soils only under conditions of high phosphorus levels attained by addition of phosphorus solution to soil (Eze and Loganathan, 1990), or when soils are treated with liming materials to enhance normal distribution of their pH values (Sato and Comerford, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the relationships between soil pH and phosphorus availability have been extensively studied on tropical soils (Mokwunye, 1975;Eze and Loganathan, 1990; Sato and Comerford, 2005; among others), and some of such studies show that the low availability of phosphorus in tropical soils is often exacerbated by the acidic nature of the soils (e.g., Sato and Comerford, 2005). Yet, as with phosphorus availability, there is paucity of data about the influence of air-drying soil samples before analysis on soil reaction in tropical soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlações positivas, negativas ou não-significativas também foram encontradas por vários autores, demonstrando efeitos complexos e, muitas vezes, antagônicos do pH sobre a sorção de P (Barrow, 1985;Geelhoed et al, 1999;Sato & Comerford, 2005).…”
Section: Efeitos Das Características Dos Solos Na Retenção E Disponibunclassified
“…Sua forma exponencial é Q = kC l/n , utilizada para calcular os valores n e k (Soares et al, 2006). Estudos têm relacionado a CMAP dos solos com o teor de argila e à superfície específica (Singh & Gilkes, 1991;Moughli et al, 1993;Pereira & Faria, 1998;Valladares et al, 2003;Rolim Neto et al, 2004), ao pH (Ernani et al, 1996;Pereira & Faria, 1998;Sato & Comerford, 2005), ao teor de matéria orgânica (Guilherme et al, 1993;Hepper et al, 1995;Berton & Pratt, 1997;Andrade et al, 2003;Moreira et al, 2006), ao Al trocável (Singh et al, 1983;Pereira & Faria, 1998;Falcão & Silva, 2004) e ao equivalente de umidade (Muniz et al, 1987). Estudando a adsorção de P em Latossolos com diferentes mineralogias, Motta et al (2002) constataram que não houve correlação significativa entre o teor de argila e a CMAP.…”
Section: Introductionunclassified